Banking and sovereign risk in the euro area - Stefan Gerlach; Alexander Schulz; Guntram B. Wolff (Deutsche Bundesbank, 2010)
We study the determinants of sovereign bond spreads in the euro area since the introduction of the euro. We show that an aggregate risk factor is a main driver of spreads. This factor also plays an important indirect role for risk spreads through its interaction with the size and structure of national banking sectors. When aggregate risk increases, countries with large banking sectors and low equity ratios in the banking sector experience greater widening in yield spreads, suggesting that financial markets perceive a larger risk that governments will have to rescue banks, increasing public debt and therefore sovereign risk. Moreover, government debt levels and forecasts of future fiscal deficits are also significant determinants of sovereign spreads.
Keywords: E43; E44; G12; 330; Sovereign bond markets; banking; liquidity; EMU; Öffentliche Anleihe; Zins; Risikoprämie; Länderrisiko; Bankenliquidität; Bankrisiko; Schätzung; Eurozone